2021
DOI: 10.3389/fnbeh.2021.639790
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Moderate Physical Activity on Brain Monoaminergic Responses to Binge-Patterned Alcohol Ingestion in Female Mice

Abstract: Monoamine neurotransmitter activity in brain reward, limbic, and motor areas play key roles in the motivation to misuse alcohol and can become modified by exercise in a manner that may affect alcohol craving. This study investigated the influence of daily moderate physical activity on monoamine-related neurochemical concentrations across the mouse brain in response to high volume ethanol ingestion. Adult female C57BL/6J mice were housed with or without 2.5 h of daily access to running wheels for 30 days. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 92 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…However, a confounding factor in these findings may be the use of running wheels. Exercise is known to influence alcohol-drinking behavior (Buhr et al, 2021; Gallego et al, 2015; Werme et al, 2002). It may be interesting for future studies to compare the effect of aberrant light conditions on alcohol intake and gene expression in the presence and absence of running wheels.…”
Section: Discussionmentioning
confidence: 99%
“…However, a confounding factor in these findings may be the use of running wheels. Exercise is known to influence alcohol-drinking behavior (Buhr et al, 2021; Gallego et al, 2015; Werme et al, 2002). It may be interesting for future studies to compare the effect of aberrant light conditions on alcohol intake and gene expression in the presence and absence of running wheels.…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, alcohol consumption had no effect on circadian locomotor activity rhythms in female rats investigated in our study, which may be attributed to the use of running wheels. It is known from previous studies in rodents that running wheel activity affects the circadian system (Leise et al, 2013;Weinert et al, 2016;Weinert and Gubin, 2022) whereas contradicting effects were found on alcohol drinking behavior in rodent models, depending on species, sex, and drinking paradigm (Ozburn et al, 2008;Ehringer et al, 2009;Piza-Palma et al, 2014;Buhr et al, 2021). It is, however, conceivable that the independent effects of the running wheel on the circadian system and/or alcohol drinking behavior mitigated the deleterious effects of the aberrant LD conditions and thus, affect alcohol intake and preference.…”
Section: Alcohol Intake Under Different Ld Schedulesmentioning
confidence: 95%
“…One nonstressed rat and one stressed rat were killed simultaneously by rapid decapitation without sedation or anesthetic, and brains were quickly extracted. Brain regions containing the prefrontal cortex, remaining caudal cortical area, hypothalamus, cerebellum, striatum, hippocampus, and hindbrain brainstem areas were rapidly microdissected on a glass plate placed over ice [for detailed methods, see our previous publications ( 35 , 36 )]. Microdissected brain areas were placed in preweighed cryovials containing 0.2 M perchloric acid, flash-frozen with liquid nitrogen, weighed again to obtain sample weights, and then stored at –80°C in an ultra-low freezer until ultra-HPLC (UHPLC) processing.…”
Section: Methodsmentioning
confidence: 99%
“…Microdissected brain areas were placed in preweighed cryovials containing 0.2 M perchloric acid, flash-frozen with liquid nitrogen, weighed again to obtain sample weights, and then stored at –80°C in an ultra-low freezer until ultra-HPLC (UHPLC) processing. Detailed UHPLC methodology for assessing monoamine-related neurochemicals can be found in our previous publications [see ( 35 , 36 )].…”
Section: Methodsmentioning
confidence: 99%